Forming of professional-pedagogical culture of future music teacher during methodical training (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the protection of physical and psychologic health of young pupils by means of mobile games.
Keywords: culture; professional-pedagogical culture; culture of music lesson; methodical training; pedagogical technologies